2020
DOI: 10.4103/jrms.jrms_414_19
|View full text |Cite
|
Sign up to set email alerts
|

Association of coronary artery dominance and mortality rate and complications in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention

Abstract: Background: Percutaneous coronary intervention (PCI) is the treatment of choice for patients with ST-segment elevation myocardial infarction (STEMI). Effect of coronary artery dominance on the patients' outcome following primary PCI (PPCI) is not fully investigated. We investigated the association of coronary artery dominance with complications and 1-year mortality rate of PPCI. Materials and Methods: In this retrospective study, patients with STEMI treated with PPCI fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This study also suffer same technical issues including small sample size and lack of adjustment for differences in key clinical factors. A study conducted by Mikaeilvand A et al 13 has similar observations as ours with no differences in success rate of procedure or complications and in-hospital as well as 1-year mortality rates between left and right dominance. However, patients with left dominant system had higher proportion of indicators of adverse outcomes such as TIMI ≤ 2 and lower left ventricular ejection fraction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study also suffer same technical issues including small sample size and lack of adjustment for differences in key clinical factors. A study conducted by Mikaeilvand A et al 13 has similar observations as ours with no differences in success rate of procedure or complications and in-hospital as well as 1-year mortality rates between left and right dominance. However, patients with left dominant system had higher proportion of indicators of adverse outcomes such as TIMI ≤ 2 and lower left ventricular ejection fraction.…”
Section: Discussionsupporting
confidence: 87%
“…However, patients with left dominant system had higher proportion of indicators of adverse outcomes such as TIMI ≤ 2 and lower left ventricular ejection fraction. 13 Multiple other studies have reported significant role of left dominance in determining the short and long term fate of patients with STE-ACS. In a study by He C et al 10 , left dominance was reported to be an independent predictor of long-term mortality with 2-year mortality rate of 2.58% against 1.23% mortality in right or codominance (p=0.024).…”
Section: Discussionmentioning
confidence: 99%
“…To reconcile our findings with the literature, we considered research publications on the prognosis after a myocardial infarction separate to publications focused on the overall burden of coronary atherosclerosis observed by dominance status. While multiple reports suggest left dominance is associated with a poorer prognosis after a myocardial infarction or revascularization procedures 9,10,37,[39][40][41][42] , the clinical relationship between dominance and coronary plaque burden or incident myocardial infarction is less clear [43][44][45] . A poorer prognosis with a left dominant circulation conditional on a plaque rupture is consistent with the intuition that an individual with a less balanced coronary circulation to the left ventricle will suffer greater damage to it when a plaque rupture occurs within a major branch especially if the rupture and thrombosis is high up in the coronary arterial tree, but this observation does not rule out the possibility that a left dominant or co-dominant circulation otherwise protects against the development of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to correlate dominance with cardiovascular events, but no consistent data has emerged 57,58,[61][62][63] . While multiple reports suggest left dominance is associated with a poorer prognosis after a myocardial infarction or revascularization procedures [56][57][58][64][65][66][67] , the clinical relationship between dominance and coronary plaque burden or incident myocardial infarction is less clear [68][69][70] . To answer these questions more definitively, large scale studies examining the relationship between dominance and an unbiased documentation of atherosclerotic burden need to be conducted, as well as robust and wellpowered Mendelian Randomization studies 60,71 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of ABO blood group with plasma lipid levels has been shown previously; the A blood group has been focused on particularly due to higher levels of serum total cholesterol and low-density lipoprotein cholesterol. [ 3 8 9 ] The ABO gene encoding glycosyltransferases with different substrate specificities to determine blood type is located on chromosome 9q34 with three variant alleles (A, B, and O). [ 10 ]…”
Section: Introductionmentioning
confidence: 99%